Practical project risk management : the ATOM methodology - Hillson, David, 1955-; Simon, Peter, 1956- (Management Concepts Press, 2012)
Get the "how" of correctly managing project risk in this latest edition of Practical Project Risk Management: The ATOM Methodology. The authors, David Hillson and Peter Simon, have applied their extensive experience in managing risk on projects to develop this simple and scalable approach-the ATOM methodology. ATOM-Active Threat and Opportunity Management-is a proven practical approach that all project managers, as well as all members of the project team, can readily understand and use. This second edition of the book reflects the authors' work to continually improve upon the model and to apply